FAKTOR IBU DAN ANAK, POLA MAKAN, ASUPAN ZAT GIZI DAN RIWAYAT INFEKSI PADA ANAK STUNTING USIA 6-23 BULAN DI WILAYAH KERJA PUSKESMAS I WANGON KABUPATEN BANYUMAS - Era Yunianingsih; Kun Aristiati Susiloretni; Sunarto Sunarto (JURNAL RISET GIZI, 2017)
Background  : Toddlers Stunting prevalence in Central Java in 2016 as much as 18.1%. Stunting prevalence in Puskesmas I Wangon in 2016 as much as 27.12%. Factors Mother and Child, Diet, Nutrition and Substance Intake Infection history is an important indicator Stunting cause.Objective : Explain relationship Mother and child factors, diet, nutrient intake and a history of infection the incidence of stunting in children aged 6-23 months working area of Puskesmas I Wangon Wangon District of Banyumas.Method : Including public nutrition research with case control approach. The research sample is Children aged 6-23 months was 50 with the distribution of 25 cases and 25 controls. Retrieval of data including data according to the nutritional status of mother and child factors, Diet, Nutrition and History Intake Infectious Substances.Results: Stunting of children aged 6-23 months with less energy intake of 15 (60%), protein intake is less than 6 (24.0%), calcium intake of less than 17 (68.0%), zinc intake less than 18 (72.0%), iron intake is less than 20 (80%). Based on the history of stunting baduta infection of 8 (32.0%) had diarrhea, and 11 (44.0%) had respiratory infection. Based on the factors Mother and Child, stunting baduta total of 14 (56.0%) had a short Mother, 21 (84.0%) Mother did not work.Conclusion: Statistical analysis showed no relationship between Height Mom (p = 0.015), there was no association between intake of energy, protein, calcium intake, intake of zinc, intake iron, diarrhea, respiratory infections, frequency of consumption, the diversity of food, education, BBL status, Apgar score, gender, occupation Mother and the Family Incomeand.